Conformation of phylogenetic relationship of penaeidae shrimp based on Morphometric and Molecular investigations - Rajakumaran, P.; Vaseeharan, B.; Jayakumar, R.; Chidambara, R. (Цитология и генетика, 2014)
Understanding of accurate phylogenetic relationship among Penaeidae shrimp is important for academic and fisheries industry. The Morphometric and Randomly Amplified Polymorphic DNA (RAPD) analysis was used to make the phylogenetic relationsip among 13 Penaeidae shrimp. For morphometric analysis forty variables and total lengths of shrimp were measured for each species, and removed the effect of size variation. The size normalized values obtained was subjected to UPGMA (Unweighted Pair-Group Method with Arithmetic Mean) cluster analysis. For RAPD analysis, the four primers showed reliable differentiation between species, and used correlation coefficient between the DNA banding patterns of 13 Penaeidae species to construct UPGMA dendrogram. Phylogenetic relationship from morphometric and molecular analysis for Penaeidae species found to be congruent. We concluded that as the results from morphometry investigations concur with molecular one, phylogenetic relationship obtained for the studied Penaeidae are considered to be reliable. Понимание точных филогенетических отношений у креветок Penaeidae важно как с общенаучной точки зрения, так и для рыбной промышленности. RAPD анализ был использован для установления филогенетических связей 13 видов креветок Penaeidae. Для морфометрических анализов измерены 40 переменных и общих длин креветок для каждого вида и устранен эффект вариабельности размера. Показатели нормализованного размера обработаны с помощью кластерного анализа UPGMA (Unweighted Pair-Group Method with Arithmetic Mean). При RAPD анализе четыре праймера показали достоверные различия между видами. Коэффициенты корреляции между паттернами ДНК использованы для построения UPGMA дендрограмм. Филогенетические связи, построенные на основе морфометрических и молекулярных анализов, совпали, что позволило сделать вывод об их достоверности.